Gestão no combate aos incêndios no sul do estado do Espírito Santo: uma análise espacial e temporal - Moro, Iulo Pessotti (2022)
The Military Fire Department is the corporation responsible for coordinating civil defense actions and for the prevention and fighting of fires, ensuring the preservation of life, the environment and heritage. The success of its operations depends directly on the response time for answering calls, so Geographic Information Systems (GIS) can provide agility in obtaining information to support decision making. The research problem observed stems from the fact that the Third Military Fire Battalion of the State of Espírito Santo (3rd BBM-ES) still uses analog maps, which hinders the planning of activities and reduces the accuracy of the representation of data, besides having a rich collection of data on fires recorded in the police reports, which are often underutilized. Thus, the main objective of this work is to georeference and analyze the spatial distribution of fire occurrences for the area of operation of the 3rd BBMES and evaluate the times spent in the stages of planning and fire fighting for the period 2017 to 2020. Regarding the methods and procedures, a quantitative approach was applied, configuring the type of research as a numerical survey, carried out in the municipalities of the 3rd BBM-ES. Vector map data georeferenced from municipal boundaries, urbanized areas and road network used to elaborate maps were obtained from government bases of free access and data on fire reports were provided by the Second Military Firefighters Company (2nd Cia BM) of the 3rd BBM-ES. The spatialization of the fire data of the occurrence reports was performed and the density was estimated using kernel for spatial distribution analysis. With the time data recorded in the occurrence reports, the time of contingent mobilization and time of firefighting was calculated. The results show that 1754 occurrences of fires were recorded distributed in the 19 municipalities of operation of the 3rd BBM-ES, of these, 1355 occurrences were recorded with geographic coordinates, enabling the analysis of the spatial distribution of fires. It was found that, for the period analyzed, 48% of the fires were recorded in urban areas, where they concentrate higher density of fires when compared to fires in rural areas, which are more dispersed, and a higher concentration of fires near highways. Cachoeiro de Itapemirim recorded 55.3% of the total occurrences of fires, with an annual average of 242.5 occurrences. It was observed that there is a high variation in the number of occurrences between the municipalities, and a smaller variation in occurrences between the years evaluated. From the results, a digitally structured geographic database was obtained as a technological product, which allows the production of thematic maps for the territory of the 3rd BBM-ES, in addition to conducting a training for access to this database.